2016
DOI: 10.1080/01480545.2016.1252919
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and cellular anti-oxidant activities of caffeic, ferulic, and p-coumaric phenolic acids: a structure–activity relationship study

Abstract: Many studies have been performed to assess the potential utility of natural products as immunomodulatory agents to enhance host responses and to reduce damage to the human body. To determine whether phenolic compounds (caffeic, ferulic, and p-coumaric acids) have immunomodulatory effects and clarify which types of immune effector cells are stimulated in vitro, we evaluated their effect on splenocyte proliferation and lysosomal enzyme activity. We also investigated the activity of natural killer (NK) cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 34 publications
2
47
0
1
Order By: Relevance
“…In this study, we tested the effect of CA on PTX-treated NSCLC H1299 cells using MTT and Annexin V-FITC/PI double staining assays and found that CA inhibited the growth and proliferation of H1299 cells in a dose-dependent manner, which is consistent with studies in other cancer cells [12][13][14][15]. However, we found that the effective concentration of CA in H1299 cells should be no lower than 500 μM.…”
Section: Discussionsupporting
confidence: 56%
“…In this study, we tested the effect of CA on PTX-treated NSCLC H1299 cells using MTT and Annexin V-FITC/PI double staining assays and found that CA inhibited the growth and proliferation of H1299 cells in a dose-dependent manner, which is consistent with studies in other cancer cells [12][13][14][15]. However, we found that the effective concentration of CA in H1299 cells should be no lower than 500 μM.…”
Section: Discussionsupporting
confidence: 56%
“…Triterpene saponins had been reported to regulate the immune function of hosts (Zhang et al., 2016). Another metabolite, 1,26‐dicaffeoylhexacosanediol that belongs to the class of organic compounds known as coumaric acid, was also with immune‐modulatory activity (Kilani‐Jaziri et al., 2017). Moreover, trans‐EKODE‐(E)‐Ib (also called 12,13‐epoxy‐9‐keto‐10‐trans‐octadecenoic acid) could be related to the inflammation regulation (Vangaveti, Jansen, Kennedya, & Malabu, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Kilani-jaziri et al, 2017). Prashanth et al, 2014 compared the immunostimulating effect of arabinoxylan and arabinoxylan with bound ferulic acid from finger millet bran.…”
mentioning
confidence: 99%